Utilizing pre-service mathematics teachers to implement effective teaching and learning practices during their field experience - AlAli, Rommel Mahmoud; Al-Barakat, Ali Ahmad (Edelweiss Applied Science and Technology, 2024)
This study aimed at analyzing the best practices for teaching and learning mathematics among pre-service mathematics teachers during their field training. The purpose is to assess how these practices align with contemporary learning standards. The sample consisted of 170 pre-service teachers from public universities in northern Jordan, selected through simple random sampling to ensure diverse representation. A structured observation checklist, comprising 37 items across four areas—constructivist-based learning, mathematical communication and representation, problem-solving and thinking development, and challenges faced by pupils. The methodology focused on observing and assessing teaching practices during field training. The findings showed that the teaching practices of pre-service mathematics teachers were generally ineffective, with most practices falling under "moderate" or "low" categories based on learning standards. Specifically, there was a lack of focus on raising active involvement in constructing mathematical concepts, which contradicts modern trends in education that promote active learning. In conclusion, the study highlights the need for enhancements in the training of pre-service teachers, recommending more intensive programs that develop innovative teaching strategies. These strategies are essential for enhancing the overall quality of mathematics education. The practical implications suggest that teacher training programs must be restructured to emphasize active learning and more effective engagement with children during mathematics instruction.